Rational causation - Marcus, Eric, 1968- (Harvard University Press, 2012)
Contemporary philosophers of mind tend to explain rationality by viewing the mind as a kind of machine--the only alternative, it has seemed, to a ghostly supernatural explanation. Marcus rejects this choice as false and defends a third way--via rational causation, which draws on the theoretical and practical inferential abilities of human beings.